Penerapan Metode Kooperatif Tipe PJBL Untuk Meningkatkan Hasil Belajar Matematika Siswa SDN 64 Parepare - St. Maryam M; Saba Pasinggi, Yonathan; Ardilla (STKIP Andi Matappa Pangkep, 2024)
This research aims to determine the improvement of student learning processes and outcomes in Mathematics subjects about flat shapes by applying the PjBL type cooperative learning method. A qualitative approach with this type of research is classroom action research (PTK). The focus of research is process focus and results focus. Carried out at UPTD SD Negeri 64 Parepare for the 2023/2024 academic year with research subjects namely 1 teacher and 16 students consisting of 7 female students and 9 male students. This research was carried out in 2 cycles. Each cycle is carried out with 2 meetings which include planning, implementation, observation and reflection stages. From the implementation of the research, data was collected using observation techniques, learning outcomes tests, and documentation. The learning results in cycle I, the learning process is at sufficient qualifications (C) and the learning test results are sufficient qualifications (C). In cycle II, the learning process is in good qualifications (B) and the learning test results are good qualifications (B). So it can be concluded that the application of the PjBL learning method can improve the learning process and outcomes in Mathematics for students in class III UPTD SD Negeri 64 Parepare.